Post-Transplant Erythrocytosis in Live Donor Kidney Transplant Recipients: A Retrospective Single Center Study - Maharjan, Suresh; Chhetri, Santosh; Khatri, Bikash; Sapkota, Nisha; Sigdel, Mahesh R (Journal of Institute of Medicine Nepal, 2020)
Introduction Post-transplant erythrocytosis (PTE) is defined as persistently elevated hemoglobin>17 g/dl and/or PCV>51% in kidney transplant recipients. The incidence of PTE varies from 5% to 17%, with occasional life‑threatening thromboembolic complications. We aimed to study the prevalence, risk factors and complications of PTE. Methods We conducted a retrospective single center study in 132 kidney transplant recipients who had undergone live donor kidney transplantation at Tribhuvan University Teaching Hospital, Nepal, between October 2017 and March 2019. Prior approval was obtained from Institutional Review Committee of Institute of Medicine. Patients with hemoglobin>17 g/dl were defined as PTE group, and others as non‑PTE group. The pattern of hemoglobin, serum creatinine, pre-transplant hemoglobin, native kidney disease, immunosuppression medications, rejection episodes, and new onset diabetes after transplantation were analyzed and compared between two groups. Results Out of the 132 kidney transplant recipients, PTE was diagnosed in 28 (21.2%) patients, out of which 27 patients (96.4%) were male and 1 (3.6%) were female with the mean time of onset at 7 months after transplantation. Patients with erythrocytosis had a relatively shorter duration of pre transplant dialysis (p=0.001). The mean pre transplant Hb and Hct in PTE group was 9.72g/dl and 30.35% whereas in non PTE group 10.02 g/dl and 31.31%. Thromboembolic and any other PTE related complications were not observed. Seventeen patients of PTE (60.7%) were treated with ACE Inhibitors and 11 (39.9%) patients did not require any treatment. Conclusion Post-transplant erythrocytosis was seen in nearly one fifth kidney transplant recipients at mean time of seven months post-transplantation; was more common in male with good graft function, and short duration of pre transplant dialysis. Response to ACE inhibitors was good.